The Influence of Social Media and Word of Mouth on Guest's Decision to Stay at Hotel Inna Parapat, Simalungun District (Case Study During Pandemic Time Covid 19) - Muhammad Hirsan Hanafi; Tina Taviani; Julianto (Politeknik Pariwisata Medan, 2021)
This study aims to determine the influence of social media and word of mouth on guest decisions to stay at the INNA Parapat Hotel, Simalungun Regency (case study during the Covid 19 pandemic). The type of data presented is quantitative. The data collection technique was done by means of a questionnaire, interview and documentation. The sample was taken as many as 85 respondents who came and stayed at the INNA Hotel Parapat. The validity and reliability of the questionnaire distributed have been tested. Data analysis used simple linear regression analysis by considering the various classical assumptions that exist, namely normality, multicollinearity and heretic plasticity to answer the formulation of this research problem, namely whether there is an influence of social media and word of mouth on guest decisions to stay at INNA Parapat Hotel, Simalungun Regency during the covid 19 pandemic) ? The results showed that the high and low social media assessments influenced the decision to stay at the Inna Parapat Hotel during the Covid-19 Pandemic, where the comparison of the t-test value for social media variables was t1count (7,501)> ttable (1.98) and in line with the significance level of 0,000. <0.05. Furthermore, the high and low assessment of word of mouth influenced the decision to stay at the Inna Parapat Hotel during the Covid-19 Pandemic, the comparison of the t-test value for the word of mouth variable was t1count (2.827)> ttable (1.98) and in line with the significance level of 0.011 < 0.05. Then with the value of Fcount (29.869)> Ftable (3.11) and in line with the significance level of 0.000 <0.05. The coefficient of determination of 42.1% of the variation in staying decisions can be explained by social media and word of mouth variables simultaneously, while the remaining 57.9% is explained by other factors, such as location variables and hotel prices. It is recommended that further research is expected to analyze other factors that influence guest stay decisions during the Covid-19 Pandemic, because there are many new factors that guests consider in choosing to stay during the Covid-19 Pandemic, such as security reasons in terms of health, restrictions tours conducted by the government, and others. In welcoming the new normal era, the hotel industry needs to be more active in marketing by utilizing technology, as an effort to reach all groups, anytime, by any means, and anywhere.